Fat Analysis of House Rat (Rattus tanezumi) in Meatball Using Gas Chromatography-mass Spectrometry (GC-MS) Combined with Principal Component Analysis - Nina Salamah; Any Guntarti; Putri Ayu Lestari; Ibnu Gholib Gandjar (Indonesian Journal of Pharmacy, 2022)
Counterfeit food products are starting to become a new problem around the people of Indonesia. Problems that are getting special attention especially the concern of contamination of food products by non-halal meat. This research aim was to analyze the fatty acids contained in house rat. The method that used was GC-MS method combined with Principle Component Analysis (PCA). Method of extraction grease was using oven at 90ºC - 100ºC for approximately one hour. After that, the derivatization process changed the fat into a methyl esters that easily evaporated. The derivatization process were using NaOCH3 and BF3. Methyl Esther compounds were injected into the chromatography instrument system GC-MS. GC-MS analysis results shows that the composition of fatty acid compounds from house rat fat with SI values > 90. Composition of fatty acids of house rat fats include: Myristate (0,19±0,03)%, Palmitoleat (2,40±0,29)%, Methyl Palmitate (27,65±0,32)%, oleate (45,81±3,25)%, and Stearate (4,65±0,28)%. Total content of house rat fatty acids was as high as 48.21% of unsaturated fatty acid and 31.49% of saturated fatty acids. The GC-MS method combined with PCA can post the fat of house rat. House rat fatty acids based on PCA's chemetrics demonstrate the resemblance of chemical physical properties with chicken fatty acids.